PRAGMATIC ANALYSIS OF TEACHER UTTERANCES IN A VIRTUAL CLASSROOM - Sari Rejeki (Universitas Pakuan, 2021)
This article is interested in studying the utterances used by a teacher in a virtual classroom. The study is conducted in Kindergarten 2 class, James Education Centre located in Bogor. The method applied is descriptive qualitative, using recordings and note taking as a technique to attain data. Looking into the illocutionary act, which is the meaning of utterances proposed by Searle, the data reveals that 69% of the teacher utterances are directives, 18% assertives and 12% expressives. The meaning of directive speech act is commiting interlocuters to do something. Assertives are used as statements and reports, while expressives as compliments and expressing gratitude. Keywords: utterance; speech act; illocutionaryact; directives.